Oats for the production of functional foods in Italy - Redaelli, Rita; Sgrulletta, Daniela; Stefanis, Ester De (MTT, 2004)
In this presentation the development of an innovative oat product for the Italian food market was revised. The work was grounded on two aspects: i) the scientific data highlighting the positive role of oat fibre components in reducing the risk of heart diseases and in influencing cholesterol and glucose metabolism; ii) the growing demand of new opportunities to increase human consumption of oats and to promote health through a higher intake of oat soluble fibre. The project was carried out across different steps. The first step involved the identification of the consumers of interest, together with the most convenient product for them. Children and elders were selected as target consumers, then alimentary pasta, traditional Italian food, was chosen as a suitable product, as both groups could get health benefits from the improvement of its nutritional value through oat enrichment. The second step was focused on the choice of the raw material to be utilised: therefore, genetic variability for the functional compounds of the oat kernel (protein, â-glucan, total dietary fibre) was explored. Both husked and naked oat cultivars were considered in this analysis, the latter resulting the most suited material for pasta production. Finally, lowinput agronomical conditions were optimised for seed multiplication, as they favoured the accumulation of functional compounds in the kernel, safeguarding at the same time the environment. In collaboration with an Italian pasta industry, an innovative oat-enriched food was developed, using natural sources (oat flour and durum wheat semolina). The oat-wheat pasta was then proposed to a panel of consumers: it showed all the qualities to be included in the market of dietetic products, as it preserved the good organoleptic characteristics of natural foods, together with a better nutritional value, due to its higher content of good-quality protein, total dietary fibre and â-glucan.
Keywords: Ka; oats; functional compounds; health promotion; pasta; Italy